Model Word Square Berbasis Traditional Games Activities di Sekolah Dasar dalam Memaksimalkan P5 - Diyah Ayu Retnoningsih; Dwi Hesty Kristyaningrum; Zahro, Umi Chabibatus Zahro (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The implementation of the Pancasila student profile strengthening project (P5) in schools needs to be implemented optimally to instill Pancasila values ​​in students. This study aims to find the effect of the implementation of the Traditional Games Activities (TGA)-based Word Square model in maximizing the Pancasila Student Profile Strengthening Project (P5) at Ta'allumul Huda Bumiayu Islamic Elementary School. This study uses a qualitative descriptive approach. The subjects in this study were fourth grade students of Ta'allumul Huda Bumiayu Islamic Elementary School. Data collection in this study was observation, interviews, and documentation. Data validity techniques used source triangulation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that through the implementation of TGA-based Word Square, students were able to achieve five of the six P5 dimensions based on the achievement of their indicators. Another P5 dimension, namely the critical thinking dimension, has not been achieved well as seen from the achievement of its indicators. This is evidenced by the achievement of cognitive factors of student groups showing that the average score of students’ answers at each game post is still below the minimum standard for the subjects of Social Sciences, Indonesian, and Religion. Psychological factors also affect students’ moods which change quickly, thus affecting the unstable level of focus on several game activities given.